Editorial in English — Revista Acústica e Vibrações nº 54
It is with great pleasure that the Editorial Committee of the Acoustics & Vibrations Journal has the honor of presenting its fifty-fourth edition (volume 37). In this issue, we continue on the path of innovation and international expansion, an effort that materializes in the welcoming of bilingual — and, boldly, trilingual — contributions, in Portuguese, Spanish, and English. It is already possible to observe the reflection of this initiative on the pages now offered to you. In this moment of transition, we still feel the remnants of the pandemic that afflicted us. However, the journal not only survives but also reinvents and strengthens itself, navigating through waters of modernization and restructuring. Despite the challenges that persist in the panorama of scientific production and the development of applied technical works, it is with enthusiasm that we note the vigorous advancement of science in acoustics, vibrations, and audio. This issue, therefore, is not just a testament to the resilience of our scientific community, but also a celebration of the incessant human desire for knowledge and innovation. We invite our readers to dive into the following pages, where they will find not only novelties but also the confirmation that, even in the face of obstacles, our journey in search of excellence and knowledge never ceases. The 54th edition of the Acoustics & Vibrations Journal